Determinación de la composición de la corriente de alimentación a un separador líquido-vapor, proveniente de un pozo de hidrocarburos, mediante el uso de modelos termodinámicos - Díaz Vigo, Juan Carlos (2009)
In the present thesis work, it was studied the accuracy of five thermodynamic models, i. e., the phi-phi model for multicomponent vapor-liquid equilibrium, and the van der Waals, Redlich-Kwong, Soave-Redlich-Kwong, and Peng-Robinson cubic equations of state, for predicting the composition of fluids coming from hydrocarbon reservoirs and fed to a flash separator in the well production stage of the petroleum and natural gas extraction industry. To achieve this, a computer program was developed, FlaSeHF, which was written in the C and C++ programming languages, and these cubic equations of state were implemented to describe the behavior of the hydrocarbon reservoir fluids liquid and gas phases being in equilibrium. Due to the fact that such fluids are hydrocarbon mixtures, it was necessary to wok with pseudocomponents for modeling the heavy fractions. In order to describe these pseudocomponent properties, the Twu, Riazi-Daubert, Cavett, and Lee-Kesler correlations were used to calculate the critical temperature and pressure, and the Lee-Kesler and Edmister correlations for the acentric factor computation. The influence of the binary interaction parameters different than zero on the results was also studied. The data entered to the program were the composition of the gas stream leaving the separator, the separator temperature and pressure, and the molecular weight and specific gravity of the heavy fraction in the gas stream, of three fluids coming from different wells, being two of them located in Peru. The results show that the best predictions were achieved with the Soave-Redlich-Kwong and Peng-Robinson equations of state, being the latter superior to the former, while the van der Waals and Redlich-Kwong equations gave very poor results and even did not converge. In addition, the Cavett correlation for calculating the critical pressure and temperature, and the Edmister and Lee-Kesler correlations for the acentric factor of the pseudocomponents, are the best correlations in the present study that allowed the convergence of the computations, yielding deviations within the 0.5% – 2% range, in the best of cases, for the value of the mol fraction of components from methane through propane. The binary interaction parameters different than zero do not influence on the calculations results, being the difference between these and those set to zero, around 1%